Acquisition and Retention: The Similar Factors Implicated in the Development and Maintenance of Reading Skill, Habit, and Preference - Kofmel, Kim G. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
Data from a recent study of adult readers suggests that genre preference formation is, like skill acquisition and habit formation, partly mediated by social, environmental and experiential factors. Preference formation can be viewed as an integral part of the reading lifetime and as a particular form of lifelong learning. Les données d'une étude récente sur les lecteurs adultes suggèrent que la formation préférentielle de genre, comme l'acquisition de compétences ou la formation des habitudes, est souvent influencée par des facteurs sociaux, environnementaux et expérimentaux. Cette formation préférentielle peut être considérée comme une partie intégrante de la lecture permanente et une forme particulière d'apprentissage continu.